A NEW RECORD OF ANISOLEPIS UNDULATUS (SQUAMATA, IGUANIDAE) (WIEGMANN, 1834) IN SOUTHERN BRAZIL (Boletín de la Sociedad Zoológica del Uruguay, 2022)
In this study we report the second record for the presence of the Anisolepis undulatus in Brazil after 179 years, at the city of Cassino, in state of the Rio Grande do Sul, approximately 100 km away from the other record in the country.
Keywords: lizard; few records; rare; low detection